Agroterrorism and the Implications of Uncertainty Reduction Theory for Agricultural Communicators - Marcus A. Ashlock; James G. Leising; D. Dwayne Cartmell II (Journal of Applied Communications, 2009)
As a consequence of various terrorist attacks on U.S. soil the vulnerability of American agriculture to an agro-terrorist attack has come into question. The objective of this paper is to view the threat of agroterrorism through the lens of uncertainty reduction theory and extend the original application of the theory from the realm of interpersonal communication to the mass communication level. We offer a brief overview of bioterrorism and agriculture and the general concepts of crisis communication and pre-crisis preparedness. We explain the relationship between the level of uncertainty and organizational crisis with the value of pre-crisis planning efforts. We show the importance of the agricultural communicator as a source of agricultural knowledge in the pre-crisis stage, which can contribute to reducing uncertainty following an agro-terrorist event.
Keywords: Research Research Agroterrorism; Implications; Uncertainty; Agricultural Communicators; organizational crisis